ASSESSMENT OF HEAVY METALS CONTAMINATION IN GROUNDWATER AND SUBSURFACE RESISTIVITY DISTRIBUTION IN ARTISANAL MINING COMMUNITIES: A COMPARATIVE STUDY OF ARUFU AND AKWANA, WUKARI LOCAL GOVERNMENT AREA, TARABA STATE, NIGERIA - Usman, Makhai; Ankidawa, Apagu; Babayi, Ahmadu; Ngasoh, Felix Gemlack (FUDMA Journal of Sciences, 2025)
This study assesses heavy metal contamination in groundwater within the Arufu and Akwana mining communities of Taraba State, Nigeria. Thirty water samples from wells (6 streams and 24 boreholes) were analyzed for heavy metals using Atomic Absorption Spectrometry. Concentrations of Pb, Fe, Cu, Cd, Ni, Zn, Sb, and Mn exceeded World Health Organization (WHO) permissible limits for drinking water, with only Cr within safe levels. Mean concentrations (mg/L) were notably high for Fe (45.08–46.37), Pb (26.46–27.01), and Ni (16.18–16.82). Pollution indices—Heavy Metal Evaluation Index (HEI), Heavy Metal Pollution Index (HPI), and Degree of Contamination —were calculated, revealing severe pollution. Mean HEI was 786.4, HPI reached 5514.3 (far exceeding the critical value of 100), and mean of degree of contamination was 8553.3, all indicating high contamination levels. Vertical Electrical Sounding (VES) further mapped subsurface pollution, corroborating the influence of mining activities. The results demonstrate that groundwater in both communities is highly contaminated and poses significant health risks, including potential carcinogenic effects, due to artisanal and small-scale mining operations. This study underscores the urgent need for remediation and stricter regulatory measures to protect water resources and public health.